Susanna Moodie's Roughing it in the Bush: A Female Contribution to the Creation of an Imagined Canadian Community - Klepač, Tihana (2010)
Identities are increasingly perceived as constituted through representation, to be understood as a “coming-to-terms-with our ‘routes’” (Hall). Hence not only should the routes be repeatedly retaken by successive generations, but it is also imperative to stay attentive to the discursive conditionality of their production and reception. Therefore Susanna Moodie’s Roughing It in the Bush is shown to reveal the regularities of discourse of the nineteenth-century colonial era: a woman writer not only struggling with the traditional masculine literary forms, but also discursively justifying its anomalous existence for which she is marginalized, yet also a woman writer very much implicated in the discourses of imperialism. It is working within those discourses that Moodie is able to progress from an exiled English lady to a Canadian settler and conceive of Canada as “home.” Hence, once it was brought into cultural circulation Roughing It in the Bush began creating an imagined Canadian community.
Projekt MZOS
ENG